The Irish pound in the EMS - O'Loghlen, B. (Statistical and Social Inquiry Society of Ireland, 1981)
On the 13th June 1980, the Central Bank of Ireland ended the transitional arrangement for the Irish pound in the EMS and allowed the pound to float up to the maximum permitted margins of the EMS. The pound is now in the same position as the other currencies in the system and is free to fluctuate over the full width of the EMS band (4Vi per cent) and to reflect market pressures up to the agreed intervention limits. The abolition of the transitional arrangements and the establishment of the IR# within the system on a comparable basis to the other members gives a useful opportunity to review some of the implications of the EMS for Ireland.
Symposium on the European Monetary System
Read before the Society, 13 November 1980
Keywords: European Monetary System; Irish pound; Fixed exchange rate regimes; Exchange rate stability; 314.15